Piezoelectric transducers temperature monitoring system in ultrasonic technological devices - Хмелев, Владимир Николаевич; Барсуков, Роман Владиславович; Генне, Дмитрий Владимирович; Абраменко, Денис Сергеевич; Ильченко, Евгений Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The article is devoted to the development of a temperature control method of piezoelectric transducers of ultrasonic vibrating systems. Temperature control is an actual task for two reasons: 1. The piezoelectric transducers efficiency can be decreased and ultrasonic equipment can be failured at noncompliance temperature mode. 2 Overheating of piezoelectric transducers may cause excessive heat of ultrasonic emitter. This is inadmissible in medical technologies The essence of this method is indirect control of the piezoelectric transducer temperature by measuring its changing of electrical capacity at the heating process. The main advantages of the proposed method are: no introduce new elements into construction; control of the temperature, not in separate areas on the surface of the piezoelectric transducer, but to consider the degree of entire piezoelectric elements heating; contactless measurement. In the article the scheme of separating the signal which is proportional to the change of capacitive piezoelectric elements current is provided. This scheme is used for practical implementation of the temperature control of piezoelectric elements. Also flowchart of a program accomplish such control is provided. In the article there is some experimental data on changing electrical capacity caused by changing piezoelectric elements temperature. The proposed temperature control system was practically implemented and tested in the ultrasonic device "Nadezhda", intended for medical and cosmetic procedures.